Integrating Theory and Practice: Contribution of the Teaching Practitioner Program in Achieving the Vision of the Physics Education Study Program - Hikmawati, Hikmawati; Susilawati, Susilawati; Doyan, Aris; Harjono, Ahmad; Nisrina, Nina (Journal of Science and Science Education, 2024)
The Teaching Practitioner Program is part of the Independent Learning-Independent Campus which is designed to bridge the gap between theory and practice in higher education. This article aims to analyze the contribution of the program in achieving the vision of Physics Education Study Program, University of Mataram, namely to develop physics education based on engineering of modern learning devices and media. This research was conducted in the even semester of 2023/2024 involving four collaborative courses with practitioners, namely School Administration and Management, Introduction to Core Physics, Thermodynamics, and Physics Learning Strategies. The research method used qualitative descriptive analysis based on final activity reports and interviews with students and lecturers. The results showed that the involvement of practitioners in teaching contributed significantly to students' understanding of the application of theory in the world of work, as well as the development of critical and adaptive thinking competencies. In addition, this program supports the mission of the Study Program in producing superior graduates who are able to develop modern learning media. It is hoped that the Teaching Practitioner Program will continue to be implemented as a strategic effort to improve the quality of physics education that is adaptive to the needs of the world of work.